Sans Pareil : Alexander Jansen, Sam Eggermont, Ilse Vareman, Kristina Minnoy, Luc Huysman. - De Markten, Brussel (Brussel : De Vlaamse Gemeenschapscommissie, 1994)
Jansen, Alexander ; Eggermont, Sam ; Vareman, Ilse ; Minnoy, Kristina ; Huysman, Luc
De Markten, Brussel, juni 1994
kunstcatalogus